Genomic testing for children with interstitial and diffuse lung disease (chILD): parent satisfaction, understanding and health-related quality of life. Issue 1 (21st February 2022) - Kelada, Lauren; Wakefield, Claire; Vidic, Nada; Armstrong, David S; Bennetts, Bruce; Boggs, Kirsten; Christodoulou, John; Harrison, Joanne; Ho, Gladys; Kapur, Nitin; Lindsey-Temple, Suzanna; McDonald, Tim; et al.
Abstract : Objective: Research is needed to determine best practice for genomic testing in the context of child interstitial or diffuse lung disease (chILD). We explored parent's and child's health-related quality of life (HRQoL), parents' perceived understanding of a genomic testing study, satisfaction with information and the study and decisional regret to undertake genomic testing. Methods: Parents of children with diagnosed or suspected chILD who were enrolled in a genomic sequencing study were invited to complete questionnaires pretesting (T1) and after receiving the result (T2). Results: Parents' (T1, n=19; T2, n=17) HRQoL was lower than population norms. Study satisfaction (T1) and perceived understanding (T2) were positively correlated (rs =0.68, p=0.014). Satisfaction with information (T1 and T2) and decisional regret (T2) were negatively correlated (T1 rs =−0.71, p=0.01; T2 rs =−0.56, p=0.03). Parents reported wanting more frequent communication with staff throughout the genomic sequencing study, and greater information about the confidentiality of test results. Conclusions: Understanding of genomic testing, satisfaction with information and participation and decisional regret are inter-related. Pretest consultations are important and can allow researchers to explain confidentiality of data and the variable turnaround times for receiving a test result. Staff can also update parents when there will be delays to receiving a result.